Open for a trusting relationship: Portuguese Parents representations regarding Day Care - Assis,Mónica (2018)
It is well established that parental involvement is a key factor for the effectiveness of Day Care practices. However, in Portugal, parental participation in Day Care is mostly passive. Indeed, parents are rarely invited to take part in school planning or being active partners in activities. Thus, we decided to collect parents opinions on Day Care aims, practices and effectiveness. For that purpose, a questionnaire was developed and applied to 170 parents (80% private schools, 62% first born, 57% girls). Our findings indicate that parents from this sample value: affectional relationships, good facilities, good material conditions/spaces, and adequate educational practices. Furthermore, parents consider Day Care as an educational setting that promotes child development, and they wish to have an open and trusting relationship with teachers. Factors such as type of school (private vs. public), and parents gender affected parents opinions. Our results suggest that parents aim to have greater involvement in their childs school and wish an open communication with teachers. These findings were later shared with teachers. Teachers expressed their surprise with some of the results and stated that in future they will create more opportunities to involve parents.